Analisis Kesalahan dalam Menyelesaikan Masalah Matematika Berdasarkan Newman’s Error Analysis Ditinjau dari Gaya Kognitif Siswa - Annurwanda, Pradipta; Heni Sutriati (Jurnal Penelitian Pendidikan, 2024)
This study aims to identify the type of student error using Newman's Error Analysis based on the type of cognitive style of students in solving set problems. This type of qualitative research uses test research instruments, questionnaires and interviews. The subjects of the study were 12 students from grade VII SMPN 03 Sengah Temila. Based on their cognitive style, research subjects are categorized into 2, namely Field Dependent (FD) and Field Independent (FI). The results showed that students with the FI cognitive style tended to make processing errors and encoding errors. Students with FD cognitive style tend to commit transformation errors and encoding errors. Students with FD cognitive style tend to commit transformation errors, processing errors, and encoding errors. Students should be given story problems that vary in problem types more often so that students get used to changing story problems into appropriate mathematical models to minimize transformation errors. To reduce process errors, students are given various story problems in the form of real cases that can be translated into diagrams, teachers demonstrate directly how to draw diagrams according to story problems, and teachers provide repeated exercises ranging from simple examples to complex examples. Students must test the final answer they have written into the story problem through a mathematical model that has been prepared at the transformation stage to reduce errors in writing the final answer.